Muscle-skeletal pain in children and adolescents potential role of backpacks - Maria Luisa Sotgiu (Publiediting, 2008)
The relationship between weight of schoolbags and muscular pain is rather controversial.This review wants to carry to acquaintance of the readers the point of view of the last reviews on the argument.